Can information help reduce imbalanced application of fertilizers in India? Experimental evidence from Bihar - Fishman, Ram; Kishore, Avinash; Rothler, Yoav; Ward, Patrick S.; Jha, Shankar; Singh, R.K. P. (International Food Policy Research Institute, 2016)
The imbalanced application of chemical fertilizers in India is widely blamed for low yields, poor soil health, pollution of water resources, and large public expenditures on subsidies. To address the issue, the government of India is investing in a large-scale, expensive program of individualizedsoil testing and customized fertilizer recommendations, with the hope that scientific information will lead farmers to optimize the fertilizer mix. We conducted a randomized controlled trial in the Indian state of Bihar in what we believe to be the first evaluation of the effectiveness of the program as currently implemented. We found no evidence of any impact of soil testing and customized fertilizer recommendations on actual fertilizer use or the willingness to pay for lacking nutrients (elicited using aBecker-DeGroot-Marschak mechanism). Several factors could be driving these results, including a lack of understanding, lack of confidence in the information’s reliability, or the costs of the recommended fertilizer mixes. We provide evidence that suggestslack of confidence is the main factor inhibiting farmers’ response